Analysis of Microbiological Test on Working Environment, Equipment and Personal Protective Equipment of Practical Students of Patient Infections - Hariyani Hariyani; Indasah Indasah; Koesnadi Koesnadi (Journal for Quality in Public Health, 2019)
Prevention of infection in dentistry hospital by dentists, dental nurses, and clinical practice students plays an important role in controlling infection including maintaining hand hygiene, use of medical gloves, safe clothes, masks, protection of eyes and head and maintaining the sterility of equipment used for treatment patient. The purpose of this study was to analyze the effect of the use of work environments, equipment and personal protective equipment on practicing students on the incidence of infection of patients in dentistry hospital IIK Kediri. The research design used is quantitative research with observational analytic methods and uses a cross sectional approach. The sampling technique used was simple random sampling with a sample of 63 work environments, equipment and Personal Protective Equipment used by students practicing at dentistry hospital IIK Kediri. The results of the research data were analyzed by logistic regression test. The results of statistical analysis with logistic regression showed p = 0,000 (p <0,05), which means that there was influence of the work environment, equipment and personal protective equipment used by students to practice the incidence of infection in dentistry hospital IIK Kediri. Dental health professionals (dentists, dentistry students) who hold dental residencies and nurses and assistants must protect themselves and patients to avoid cross infection, cross contamination and work safety in dental practice